Modeling of Hybrid-Renewable Energy Sources of Linear Load System - Ramesh, T.; Ragothaman, V.; Saravanan, R.; Emayavaramban, G.; Prakash, P. (International Journal of Engineering and Technology, 2018)
A representation of mixture power system based on a photovoltaic, airstream system, a battery bank, and a DC motor-pump is established in this work. The major purpose is to get together the power load requirements through successful employment of the batteries. In this employment, recognition and reproduction of a hybrid solar, wind and storage battery power system is offered. This procedure likewise incorporates a battery stockpiling DC source convert to air conditioning supply to stack through an inverter. The proposed control approach has been embedded by recreation under the equivalent metrological conditions, demonstrating the adequacy of the proposed half and half framework. Reenactment results gotten by MATLAB/SIMULINK programming are displayed.Â  Â